Simulation of gasification of hydrocarbons-enriched biomass - Caballero-Chavarría, Andrey (2019)
Gasification is a thermochemical process in which organic raw materials are converted into gases containing H2 and CO (syngas), which can be used to obtain products such as electricity, fuels and other chemicals. It is influenced by characteristics of the system where the thermal conversion takes place, the operating conditions and the raw materials used. It was simulated a process of gasification of hydrocarbons-enriched biomass in which the gases generated are used for electricity generation, to evaluate the use of such raw materials. A non-stoichiometric gasification model, the Peng-Robinson equation of state as well as known gasification reactions were used. A downdraft gasifier was considered working with 22 kg/h of mix feed 3:1 biomass: hydrocarbons, 20 kg/h of air (gasifying agent), 1 atm of absolute pressure and gasification temperature of 900-1000 °C. The gases generated are composed of 27.44 % H2, 39.79 % CO, 5.73 % CH4, 0.1 % CO2 and 27.01 % N2. The net power of the gasifier is 27.82 kW and the consumption of the mixture 3:1 biomass:hydrocarbons 0.79 kg/kWh. The addition of hydrocarbons to biomass improves the characteristics of the syngas obtained and reduces the raw material requirements for the operation of the gasifier. The mixture 3:1 biomass:hydrocarbons is adequate for the performance of the process, allowing to take advantage of wastes that otherwise would have to be disposed of and treated, generating energy, environmental and economic benefits.